The Relevance of Non‐Income Tax Relief* - Drake, Michael S.; Hess, Ryan V.; Wilde, Jaron H.; Williams, Braden M. (Contemporary Accounting Research, 2022)
ABSTRACT Governments regularly offer non‐income tax relief to attract business investment. However, it is unclear whether or how markets impound information about the relief into security prices. We use novel data from retrospective public records to examine the information content of non‐income tax relief. We predict and find that the receipt and magnitude of this relief are both strongly associated with recipients' future accounting performance and future abnormal returns. We further find that abnormal returns associated with the relief cluster around future earnings information events. In combination, this evidence suggests that non‐income tax relief is value‐relevant but is incorporated into prices over time.